Common Factors of Generalized Fibonacci, Jacobsthal and Jacobsthal-Lucas numbers - Gupta, V. K.; Panwar, Yashwant Kumar (International Journal of Applied Mathematical Research, 2012)
In this paper, we present some identities involving common factors of generalized Fibonacci, Jacobsthal and Jacobsthal-Lucas numbers. Binet’s formula will employ to obtain the identities.